A Pseudo-parabolic Type Equation with Weakly Nonlinear Sources (Journal of Partial Differential Equations, 2020)
In this paper, we prove the existence of nonnegative solutions to the initial boundary value problems for the pseudo-parabolic type equation with weakly nonlinear sources. Further, we discuss the asymptotic behavior of the solutions as the viscous coefficient k tends to zero.